2004
DOI: 10.1097/00008469-200404000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomaviruses and cancer in Uganda

Abstract: In a case-control study in Uganda, we examined associations between different cancer sites or types in relation to antibodies against human papillomaviruses (HPV)-16, -18 and -45. For each cancer site or type, the control group comprised all other cancers excluding those known, or thought to be associated with HPV infection (cancers of the uterine cervix, penis and eye). Among controls the seroprevalence of antibodies was 11% (68/616) against HPV-16, 5% (29/605) against HPV-18 and 6% (35/605) against HPV-45. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…Notably, though, transient HPV infections do not elicit seroconversion, and some women with persistent infection fail to seroconvert (5). Within Africa, a Ugandan study found HPV-16 antibodies significantly associated with cancer of the cervix (20). The present study constituted the first assessment in southern Africa, and possibly the rest of Africa, of cervical HPV infection, as well as HPV-16 antibody prevalence and associated risk factors, in a large population (Ͼ1,000).…”
mentioning
confidence: 65%
“…Notably, though, transient HPV infections do not elicit seroconversion, and some women with persistent infection fail to seroconvert (5). Within Africa, a Ugandan study found HPV-16 antibodies significantly associated with cancer of the cervix (20). The present study constituted the first assessment in southern Africa, and possibly the rest of Africa, of cervical HPV infection, as well as HPV-16 antibody prevalence and associated risk factors, in a large population (Ͼ1,000).…”
mentioning
confidence: 65%
“…A careful correlation of these mixtures and the presence of HPV are also necessary to weight the role of these neoplasms in the viral pathway of carcinogenesis. Associated studies using HPV serology markers support a strong relationship between HPV and SCC penile cancer, with odds ratios ranging from 1.7 to 6.4 12 37 44 54 55…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it has been shown that the cell-mediated immune response cleared the majority of HPV infections within 1–2 year’s exposure [14]. Despite the fact that a number of seroprevalence studies have been conducted in resource-rich countries and some in resource-poor countries [1518], no such data appears to be available from the Arab world.…”
Section: Introductionmentioning
confidence: 99%